(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes the current state of the development of communicative speech in elementary school students by means of media technologies. The article examines the impact, opportunities and problems of media technologies on the formation of children’s speech in the 21st century. Examples include various game programs, video and audio materials, online communication platforms, creative programs and educational games used in the educational process. At the same time, the article talks about the important role of teachers and the need to improve their skills for the effective and safe use of media technologies. The article emphasizes the importance of using media technologies in the development of communicative speech in elementary school students, as well as the need to solve problems in this regard.